Deciphering the Key Toxicants and Hepatotoxicity Mechanisms of Epimedii Folium and its Preparations via Network Toxicology and Molecular Docking - Huang, Lijun; Huang, Jie; Shen, Xin; Shen, Baoying; Yang, Chunqi; Wang, Zhixing; Xiao, Chengrong; Lai, Chengcai; Gao, Yue (Combinatorial Chemistry & High Throughput Screening, 2026)
<span class=
Keywords: hepatotoxicity